A Modified Murine Calvarial Osteolysis Model Exposed to Ti Particles in Aseptic Loosening. - Deng, Zhantao; Wang, Shuai; Li, Mengyuan; Fu, Guangtao; Liu, Chang; Li, Shuxian; Jin, Jiewen; Lyu, Feng-Juan; Ma, Yuanchen; Zheng, Qiujian (BioMed Research International, 2020)
Aim. To investigate the different effects on osteolysis between commercial pure Ti particles and TiAl6V4 particles obtained from prosthesis of patients with aseptic loosening. Method. Scanning electron microscope, energy dispersive X-ray spectrometry, and X-ray diffraction were used for the size test, chemical composition test, and phase analysis of two kinds of Ti particles. Microcomputed tomography (micro-CT) and 3-dimensional reconstruction analysis were applied to analyze the bone loss quantitatively and radiologically. Hematoxylin-eosin (HE) staining and tartrate-resistant acid phosphatase (TRAP) staining were used to assess the histologic difference. Result. TiAl6V4 particles were constituted by FeO, Al45V7, and Al3Ti while pure Ti particles were constituted by Ti, Ti3O, and C4H7NO3. Similar particle size of nanoscale was detected of two Ti particles. A TiAl6V4 osteolysis model had more severe bone loss when scanned with micro-CT and assessed by quantitative analysis. TiAl6V4 also presented deeper and wider calvarial bone loss in HE staining and more activated osteoclasts in TRAP staining. Conclusion. A mouse calvarial model is the most effective animal model for the primary in vivo research of aseptic loosening. Compared with commercial Ti particles, TiAl6V4 particles derived from prosthesis of an aseptic loosening patient had more severe bone loss and more activated osteoclast, which was more consistent with pathogenesis of aseptic loosening in vivo, had high success rate of establishment of a model, and was more desired in animal modeling.